Quantitative proteogenomic profiling of epidermal barrier formation in vitro. Issue 3 (June 2015) - Winget, Jason M.; Watts, Julian D.; Hoopmann, Michael R.; DiColandrea, Teresa; Robinson, Michael K.; Huggins, Tom; Bascom, Charles C.; Isfort, Robert J.; Moritz, Robert L.
Highlights: Proteomics and transcriptomics were performed for a model of epidermal development. 3661 proteins were identified across three developmentally crucial time points. Quantitation revealed over 1200 differentially abundant proteins. 574 proteins matched transcript abundance on a rank-order basis. Abstract: Background: The barrier function of the epidermis is integral to personal well-being, and defects in the skin barrier are associated with several widespread diseases. Currently there is a limited understanding of system-level proteomic changes during epidermal stratification and barrier establishment. Objective: Here we report the quantitative proteogenomic profile of an in vitro reconstituted epidermis at three time points of development in order to characterize protein changes during stratification. Methods: The proteome was measured using data-dependent "shotgun" mass spectrometry and quantified with statistically validated label-free proteomic methods for 20 replicates at each of three time points during the course of epidermal development. Results: Over 3600 proteins were identified in the reconstituted epidermis, with more than 1200 of these changing in abundance over the time course. We also collected and discuss matched transcriptomic data for the three time points, allowing alignment of this new dataset with previously published characterization of the reconstituted epidermis system. Conclusion: These results represent the most comprehensive epidermal-specific proteome to date, and therefore reveal several aspects of barrier formation and skin composition. The limited correlation between transcript and protein abundance underscores the importance of proteomic analysis in developing a full understanding of epidermal maturation.